Pengantin Pesanan Pos (Mail Order Bride): Modus Operandi Human Trafficking di Indonesia - Lessy, Zulkipli (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
Marriage for some people is a sacred thing: it is a part of the important forms of worship of God. The sacredness, nevertheless, to some extent disappears when the marriage mainly becomes a trap that concludes with prostitution and slavery. This article examines mail-order bride as a form of human Â trafficking. Women in this kind of trafficking are primarily trafficked for prostitution industries. The mail,order bride arrangements occur in Indonesia and, also, in many countries in South Asia and Southeast Asia, including Pakistan, Bangladesh, Nepal, Vietnam, and Malaysia. This form of trafficking is more difficult to deal with because of its hidden schema: marriage is commonly considered an individual privacy wherein outsiders cannot easily interfere.